Benthic Molluscs Communities in the Intertidal Coast of Tanimbar Islands, West Southeast Mollucas - Heryanto, Heryanto (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTThis paper presents the results of a survey on intertidal molluscs in 3 habitats (Seagrass bed, coral reef, and sandflat) in Tanimbar Islands of West South-east Moluccas, Indonesia. Six relatively large and two small islands were attained to perform 125 plots of 34 stations. Molluscsâ diversity in each habitat were calculated using Shannon-Wiener formulation whereas Mann-Whitney formulation for comparing between habitats. Multivariate analyses for clustering of PAST 2.17 was utilized to further the analyses. A number of 101 species gastropods (26 families) and 51 species of bivalves (19 families) were recorded. Seagrass bed was inhabited by 100 species, followed by coral reef by 85 and sandflat by 44 species. Shannon-Wiener indexes for molluscsâ diversity range in seagrass was 0.39 to 1.29, in coral was 0.27 to 1.14 and in sandflat was 0.52 to 0.99. Clustering analyses for stations revealed that three stations in seagrass were the most dissimilar, followed by one station in coral due to habitat. Clustering analyses for species found four dissimilar groups of molluscs, whereas a group has many consimilar members.Keywords: Seagrass, coral, sandflat, diversity, clustering